Diagnostic value of risk malignancy index (RMI) for detection of malignancies in clinically diagnosed ovarian masses and to evaluate the validity of individual constituent parameter of risk malignancy index - B., Jenitha; M., Subbiah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pre-operative knowledge regarding the nature of ovarian mass is necessary in order to plan surgery. Risk malignancy index (RMI) is a simple scoring system based on three factors serum CA 125, USG score and menopausal status. The RMI was interpreted as 1) score >250=high risk, 2) 25-250=intermediate risk, 3) score <25=low risk. The objective of the study was to evaluate risk malignancy index (RMI) in pre-operatively clinically diagnosed ovarian mass and to compare the validity of individual parameter in RMI i.e. menopausal status, serum CA 125 and USG score to differentiate the nature of clinically diagnosed ovarian masses as benign or malignant. Methods: This was an observational study conducted in the Department of obstetrics and gynaecology, Trichy SRM Medical College and Research Centre, Trichy from January 2017 to January 2018 with a sample size of 77 cases with clinical diagnosis of ovarian mass admitted for surgery. The validity of RMI and validity of individual parameters were calculated and compared. Results: A total of 77 patients with ovarian tumors were enrolled in this study. According to the histological examination of the surgical specimens of the 77 women, 27.3% (n=21) had malignant tumors and 67.7% (n=56) had benign disease. Most common benign tumour was serous cystadenoma and the most common malignant tumour was mucinous cystadenocarcinoma. Among 77 patients, 42.85% (n=33) were postmenopausal, 44.15% (n=34) had USG score of 4, 27.27% (n=21) had serum CA125 level >cut-off values and 27.27% (n=21) had RMI >250. In cases where RMI>250, 18 out of 21 were malignant. In cases where USG score was 4, 19 out of 34 were malignant. Of the cases where serum CA125 level was > cut-off values 16 out of 21 were found to be malignant. RMI showed better sensitivity of 85.71%, specificity of 94.64%, PPV of 85.71%, NPV of 94.64% and diagnostic accuracy of 92.20%. Conclusions: RMI is highly valuable and reliable in differentiating benign and malignant ovarian lesions and facilitates selection of cases for conservative management and oncology referral.